Anticoagulant rodenticides in mesocarnivores around the world: A review - David Fernández-Casado; Javier García-Muñoz; Ángel Portillo-Moreno; Salomé Martínez-Morcillo; María Prado Míguez-Santiyán; Marcos Pérez-López; Francisco Soler-Rodríguez (Environmental Chemistry and Ecotoxicology)
Anticoagulant rodenticides (ARs) have been the main tool to control rodent pests since the 1950s; however, they can affect “non-target” species causing serious environmental problems, such as secondary poisonings in wildlife by an indirect route of exposure. Mesocarnivores are the second group of wild animals most affected by ARs poisoning, only preceded by raptors, with dire incidence values in the literature: 63.78% of the studied animals were exposed to ARs. This exposure is mainly due to life history traits, such as diet (increasingly based on rodents and micromammals), ethology (opportunistic animals, scavenging), and adaptations to the anthropized environment. In this review, we have compiled data from over 40 studies from 17 countries from the 1990s to the present. A total of 11 different ARs were analyzed. Brodifacoum had the highest detection incidence (56.31%). In some cases, several ARs were detected in the same animal. Secondary intoxication (from food based on ARs target species or their carcasses) is the main type of AR intoxication in mesocarnivores. Among the most affected species are the fox (Vulpes vulpes) (Europe) and the fisher (Pekania pennanti) (an endangered mustelid in the USA). In most cases, the AR concentrations in the liver exceeded the diagnostic threshold (100–200 ng/g wet weight), although sublethal exposure was also a problem. The impact of ARs on mesocarnivore populations is unknown, mainly because of the lack of specific studies which usually focus on other species that are of “greater interest” because of biological, economic, or social reasons. In addition, there is a lack of research on the toxic effects of sublethal exposure to ARs, which may contribute to the death of predators. More exhaustive analysis and study of the real implications of ARs on the world's mesocarnivores and the application of mechanisms to mitigate exposure, as well as the search for new alternatives for pest control, are therefore needed.